Effect of maqui-berry extract in dry eye disease - A clinical and molecular analysis - Kundu, Gairik; Shetty, Rohit; D'Souza, Sharon; Gorimanipalli, Bhavya; Koul, Ameeta; Sethu, Swaminathan (Indian journal of ophthalmology, 2023)
Purpose: This study aims to investigate the effects of maqui-berry extract (MBE) in improving signs and symptoms of dry eye disease (DED) along with ocular surface inflammation in patients with DED. Methods: Twenty patients were randomly assigned to a MBE or a placebo group (PLC). DED parameters including Schirmer's test 1 (ST1), tear film break-up time (TBUT), ocular surface disease index (OSDI), and corneal staining were assessed before treatment and 2 months post-treatment. Tear fluid samples before and after treatment from a subset of these patients were collected from the study subjects using sterile Schirmer's strips, and the levels of interleukin (IL)-1β, IL-10, IL-6, IL-17A, tumor necrosis factor-α (TNFα), matrix metalloproteinase-9 (MMP9), soluble intercellular adhesion molecule-1 (sICAM1), and vascular endothelial growth factor-A (VEGF-A) were measured using a microfluidic cartridge-based multiplex ELISA. Results: The MBE group demonstrated a significant (p < 0.05) decrease in OSDI scores along with a significant increase in Schirmer's test 1 compared to the PLC group. No significant change in TBUT and corneal staining was observed between the study groups. Levels of proinflammatory factors such as IL-1β, IL-6, IL-17A, TNFα, and MMP9 were observed to be significantly reduced, along with a significant increase in IL-10 levels following treatment in the MBE group compared with the PLC group. Conclusion: Consumption of MBE resulted in the resolution of DED signs and symptoms, along with a reduction in ocular surface inflammation.